Calidad De Sistemas De Información - SI430 - 202102 - Quispe Tuesta, Julio Enrique (2021)
Description: Information is one of the most valuable organizational assets, because of that, sophisticated information systems are being used for capturing, storing, processing and distributing information inside and outside companies. So, information systems look for satisfying information requirements of organizations, or, in other words, achieve a high degree of quality. In the first two units, it is covered the main concepts of quality management and quality management systems. Then, in unit three, information systems and how quality is managed in each stage of their life cycle are studied. Finally, in unit four, main frameworks for information technology service management are reviewed through the lens of quality management. Purpose: The course Information Systems Quality was designed to allow students understand the impact of information systems inside and outside the organization, so that, they can design and implement solutions which add value to organizations and society, by taking ethical decisions. This course contributes to writing communication competency (level 3), and specific competency (5): Work in multidisciplinary teams (level 2). It requires students to approve the course Enterprise Systems Implementation (SI409).